Optimization of Occupational Safety and Health Implementation in a Chemical Analytics Laboratory - Risqi Adinda Sari; Teguh Satrio (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: A Laboratory room is one of the places that has the potential for the occurrence of work accidents for its users. A chemical analytics laboratory in University X Surabaya is a means for lecturers or students to conduct research using certain tools and materials, so occupational safety and health management is needed to minimize the risk of harm in the laboratory. This study aims to describe the application of occupational safety and health in the chemical analytics in University X Surabaya. Methods: This research used a qualitative approach. This type of research was descriptive observation, conducted by observing the safety checklist of the chemical analytics laboratory of University X Surabaya in August 2020 and observing the situation in the laboratory directly. Results: In the occupational safety and health checklist in the chemical analytics laboratory there are 8 indicators (laboratory rooms, storage facilities, sanitation, personnel facilities, heating and ventilation, lighting, laboratory safety, service, and fire prevention and protection), with 65 question points to be met. Based on the observations, 13 points have not been met and 49 points have met the checklist. Meanwhile, the other 3 points are still not filled out. Conclusion:The application of occupational safety and health in the chemistry analytics laboratory in University X Surabaya is good enough because most of the questions on the checklist have been met.Keywords: implementation, laboratory, occupational safety and health